Compatibility of Geosynthetic Clay Liners with Three Pennsylvania Municipal Solid Waste Leachates. Issue 5 (1995) - Narejo, D.B.; Memon, G.Q.
Abstract : The free swell of three commercially available geosynthetic clay liners is evaluated using the Geosynthetic Research Institute test method GCL 1. Leachate from three Pennsylvania municipal solid waste landfills is used in the test procedure. It is seen that the swelling of all three geosynthetic clay liners is significantly affected by the composition of the landfill leachates; however, the magnitude of the decrease in swelling varies with each leachate. Since the permeability of clays is inversely related to their swell potential, a significant drop in free swell may indicate an increase in permeability. Therefore, a significant drop in free swell as compared to de-ionized water may indicate incompatibility of a geosynthetic clay liner with the service environment in question.